2020
DOI: 10.1186/s43055-020-00268-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between contrast-enhanced mammography, tomosynthesis, and breast ultrasound as complementary techniques to mammography in dense breast parenchyma

Abstract: Background: Mammography is accused of having low sensitivity and specificity in dense breast parenchyma. Also, women with dense breasts show an increased risk of developing breast cancer. Breast ultrasound has been used for several years for a better characterization of breast lesions. Contrast-enhanced mammography and tomosynthesis are relative novel imaging techniques that have been implicated in breast cancer detection and diagnosis. We aimed to compare breast tomosynthesis, contrast-enhanced mammography, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…A total of 827 patients with 958 lesions, ranging in age from 15 to 78 years, were included. Among the included studies, three 11 , 15 , 19 were retrospective studies, and the remaining seven 12 , 13 , 14 , 16 , 17 , 18 , 20 were prospective studies. Table 1 and Additional Files S2 and S3 show the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 827 patients with 958 lesions, ranging in age from 15 to 78 years, were included. Among the included studies, three 11 , 15 , 19 were retrospective studies, and the remaining seven 12 , 13 , 14 , 16 , 17 , 18 , 20 were prospective studies. Table 1 and Additional Files S2 and S3 show the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 11 , 12 , 13 , 15 , 17 , 18 , 20 reported the CEM findings of benign and malignant lesions. In the analysis of 609 lesions, the relative malignancy OR value of the enhanced lesions was 28.11 (95% CI, 6.84–115.48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast ultrasound is a non-invasive, relatively available imaging modality that is used as complementary to mammography in screening especially in dense breasts, differentiation of solid and cystic lesions, characterization of lesions, and diagnosis of intraductal mass as well as problem-solving for mammographically detected asymmetries [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…According to European Society of Breast Imaging recommendations mammography is a basic diagnostic method of clinically asymptomatic breast cancer [1]. However, it is worth remembering, that sensitivity and specificity of mammography is limited, mostly by dense breast anatomy [2,3]. Therefore, other modalities are applied, such as ultrasonography and MRI [4,5].…”
Section: Introductionmentioning
confidence: 99%